(untitled) (Altre Modernità, 2023)
The essay offers some insights into the ways in which some ideas arise, spread and consolidate themselves within a collectivity of people, with outcomes that are useful in fostering a sense of social cohesion. In parallel, it discusses the reasons why in certain cases a representation is contested, debated and generates conflicts and controversies, fostering a sense of uncertainty and social fragmentation.